Weight awareness among medical students - Nijhawan, Dushyant M.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2018)
Background: Overweight and obesity is a global issue. It needs to be tackled at adolescent and young age. Aim of our study was to evaluate weight awareness, prevalence of overweight and obesity in medical students. Methods: 200 medical students of 18-20 years were included in this cross-sectional study. Results: Out of 100 girls, 51 (51%) girls had normal BMI, 19 (19%) were overweight, 17 (17%) girls were obese while 13 (13%) girls were underweight. Out of 100 boys, 66 (66%) boys were having normal weight, 16 (16%) boys were underweight, 14 (14%) boys were overweight and 4 (4%) boys were obese. Sixty-one (61%) girls were doing exercise >3 times in a week while 39 (39%) girls were doing exercise <3 times in a week. Out of 100 boys, 44 (44%) boys were doing exercise <3 times in a week while 56 (56%) boys were doing exercise >3 times in a week. Conclusions: Issue of overweight and obesity needs to be focused more.